Rapid Serological Tests and Immunity Policies: Addressing Ethical Implications for Healthcare Providers and the Healthcare System as a Priority - Masella, Marie-Alexia; Gallois, Hortense; Bélisle-Pipon, Jean-Christophe (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
Healthcare providers (HCP) have been central actors in containing the COVID-19 pandemic. Although potentially very beneficial, the implementation of large-scale rapid serological tests raises ethical dilemmas and affects HCPs’ capacity to work in optimal conditions. In this regard, we call for attention to address specific and urgent ethical issues distinctively affecting HCPs following the availability and possible mandatory use of rapid serological tests for COVID-19.